Circulating fibroblast activation protein and dipeptidyl peptidase 4 in rheumatoid arthritis and systemic sclerosis. (19th December 2016) - Sinnathurai, Premarani; Lau, Wendy; Vieira de Ribeiro, Ana Julia; Bachovchin, William W.; Englert, Helen; Howe, Graydon; Spencer, David; Manolios, Nicholas; Gorrell, Mark D.
Abstract: Aim: To quantify circulating fibroblast activation protein (cFAP) and dipeptidyl peptidase 4 (cDPP4) protease activities in patients with rheumatoid arthritis (RA), systemic sclerosis (SSc), and a control group with mechanical back pain and to correlate plasma levels with disease characteristics. Methods: Plasma was collected from patients with RA ( n = 73), SSc ( n = 37) and control subjects ( n = 26). DPP4 and FAP were quantified using specific enzyme activity assays. Results: Median cDPP4 was significantly lower in the RA group ( P = 0.02), and SSc group ( P = 0.002) compared with controls. There were no significant differences in median cFAP between the three groups. DPP4 and FAP demonstrated a negative correlation with inflammatory markers and duration of disease. There were no associations with disease subtypes in RA, including seropositive and erosive disease. Decreased cDPP4 was found in SSc patients with myositis. Plasma FAP was lower in RA patients receiving prednisone ( P = 0.001) or leflunomide ( P = 0.04), but higher with biologic agents ( P = 0.01). RA patients receiving leflunomide also had decreased cDPP4 ( P = 0.014). SSc patients receiving prednisone ( P = 0.02) had lower cDPP4 but there was no association with cFAP. Conclusions: No association was found between cFAP and RA or SSc. Plasma DPP4 was decreased in RA and SSc when compared with controls. cDPP4 and cFAP correlated negatively with inflammatory markers and there were no significant correlations with disease characteristics in this RA cohort.